Redescription of Korotkevitschia pelagica (Korotkevitsch, 1961) (Enopla: Hoplonemertea: Cratenemertea), a pelagic nemerteann from Antarctica - Chernyshev, Alexei V. (Zootaxa, 2005)
The anatomy of the holotype of the Antarctic hoplonemertean, Korotkevitschia pelagica, is redescribed and illustrated. The systematic position of the species is discussed. A new, extended, diagnosis is provided for the epipelagic cratenemertid family Korotkevitschiidae, which includes the genera Korotkevitschia and Achoronemertes and an undescribed species, referred to as Atlantic H”.